Math, asked by IᴛᴢBʟᴜsʜʏQᴜᴇᴇɴ, 10 months ago

Pls answer fast with EXPLANATION i will surely mark as brainliast and thanks.​

Attachments:

Answers

Answered by swagstaraarav2210
3

Answer:

a> x^2+4xy+y^2

b> -a+15b+26

c> 2x^2-5y^2+11xy

Step-by-step explanation:

a> (x^2+xy+y^2)-(z)= 2x^2+3xy

   z= (2x^2+3xy)-(x^2+xy+y^2)

   z= (2x^2-x^2)+(3xy+xy)+(y^2)

   z= (x^2)+(4xy)+(y^2)

   z= x^2+4xy+y^2

b>  (2a+8b+10)-(z)= -3a+7b+16

     z= 2a+8b+10+(-3a+7b+16)

     z= 2a+8b+10-3a+7b+16

     z= (2a-3a)+(8b+7b)+(10+16)

     z= -a+15b+26

c>   (3x^2-4y^2+5xy-20)-(z)= (-x^2-y^2+6xy+20)

      z= (3x^2-4y^2+5xy-20)+(-x^2-y^2+6xy+20)

      z= 3x^2-4y^2+5xy-20-x^2-y^2+6xy+20

             *-20+20= 0

      z= (3x^2-x^2)-(4y^2-y^2)+(5xy+6xy)+(0)

      z= 2x^2-5y^2+11xy

Answered by premapallak
4

plz you too follow me ,dont feel bad bcoz following and unfollowing I just wanted you to say plz follow me back

It's Blushy queen plz ..

Similar questions